Exergy-based industrial ecology assessment of integrated and separated power and heat production systems. (25th July 2011) - Abusoglu, Aysegul; Kanoglu, Mehmet
In this paper, exergy-based industrial ecology concept is demonstrated in terms of exergetic rate of resource depletion by analysing two different combined heat and power productions systems: the CGAM system and a Diesel Engine Powered Cogeneration (DEPC) system. The analysis indicates that exergy-based industrial ecology concept can be successfully applied to cogeneration systems, demonstrating advantages of integrated generation. The weighted depletion number for separate productions of electricity and steam is determined to be 0.673 whereas the value for the integrated CGAM system is 0.532. The corresponding depletion numbers for the DEPC system are determined to be 0.590 and 0.480, respectively. It is clear from these numerical results that separate power and heat production system causes greater non-renewable resource depletion when compared with integrated systems.